Collision Energy Dependence of Hypertriton Production in Au+Au Collisions at RHIC - Li Xiujun (EPJ Web of Conferences)
Hypernuclei are bound states of nucleons and at least one hyperon. In particular, the hypertriton Λ3H, a bound state consisting of a proton, neutron and hyperon, is the lightest known hypernucleus. Precise measurements on the energy dependence of Λ3H production will give invaluable information on hypernuclei production mechanisms due to its unique intrinsic properties. The second phase of the Beam Energy Scan (BES-II) at RHIC provides a great opportunity to study hypernuclei production. In these proceedings, we present pT-integrated yields (dN/dy) at mid-rapidity, yield ratios and average transverse momentum (<pT>) of Λ3H as a function of collision energy in Au+Au collisions from √sNN = 3 to 27 GeV. These results are compared with phenomenological model calculations, and physics implications on production mechanism are discussed.